Islamic Securities Crowdfunding: A Bibliometric Analysis - Zidan, Muhamad; Irfany, Mohammad Iqbal (SMART Insight, 2023)
Research focuses on Islamic Securities Crowdfunding topic by using a bibliometric analysis approach. In this study, 81 Scopus-indexed journal articles were analyzed to measure scientific performance in this domain. The bibliometric analysis process includes identifying the research background and determining key indicators. The results of this analysis visualized the author network, country of origin, related institutions, and keyword trends. Malaysia was identified as the dominant country in the research of Islamic Securities Crowdfunding, demonstrating its significant role. There are at least 6 (six) research clusters related to this topic. The findings provide a deeper understanding of the contribution of researchers, the role of countries, and institutions in this sub-ecosystem, providing a basis for future strategy development, especially regarding blockchain technology.